Competitive/comparative governance mechanisms beyond marketization: A refined concept of competition in education governance research. (January 2022) - Madsen, Miriam
Much contemporary scholarship claims that competition has become a key characteristic of educational governance, and that competition occurs in educational governance as a consequence of the comparative turn in education. This article problematizes the widespread application of the concept of competition as a relevant term across (seemingly) all governance contexts, and seeks to overcome this problem by theorizing competition as an entangled phenomenon that takes on a different ontology according to the specific situations in which it occurs. This theorization highlights three dimensions of competition that may affect its ontology: the field of contestants, the rules of the game, and the competition objective. The result is an analytical framework that makes the concept of competition sensitive to different governance contexts across Europe and the Western world, including those with strong remnants of universalistic welfare state models. The analytical framework allows for a distinction between market-based competition and competition as a governance instrument that mediates managerial decision-making in which the contestants fight to avoid top-down reform rather than fighting against their peers. The analytical framework implies that we cannot characterize all European education systems as governed through competition-based mechanisms without caution and further specification.